The Influence of Student Learning Styles on Student Achievement and Intelligence - Nurdin Arifin; Mutohharun Jinan; Muthoifin; Bello Ali (Walidem Institute and Publishing (WIP), 2023)
This study aims to determine the influence of learning styles on student achievement. This study used a quantitative approach. This type of research is field research. The population in this study was all grade VIII students of SMP Muhammadiyah 6. The data collection method uses a Likert scale model questionnaire to determine the type of student learning style, while the Akidah Akhlak learning achievement variable uses school documentation in the form of report card scores. The data analysis method used to test the hypothesis is multiple linear regression analysis. The results showed that: (1) There is a significant influence between Visual Learning Style on Akidah Akhlak Learning Achievement, which means that the better the Visual, the Learning Achievement will increase. (2) There is a significant influence between Auditory Learning Style and Learning Achievement, which means that the better the Auditory, the Learning Achievement will increase. (3) There is a significant influence between Kinesthetic Learning Style and Learning Achievement, which means that the better Kinesthetic Learning Achievement will increase. (4) The test results of multiple linear regression analysis obtained a calculated F value of 7.235 with a significance value of 0.000 (0.000 < 0.05), meaning that Ha is accepted and H0 is rejected. This means that the hypothesis that states